2018
DOI: 10.1073/pnas.1805787115
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of nutrient flows in island ecosystems following human colonization evidenced by isotopic analysis of commensal rats

Abstract: The role of humans in shaping local ecosystems is an increasing focus of archaeological research, yet researchers often lack an appropriate means of measuring past anthropogenic effects on local food webs and nutrient cycling. Stable isotope analysis of commensal animals provides an effective proxy for local human environments because these species are closely associated with human activities without being under direct human management. Such species are thus central to nutrient flows across a range of socionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…There is a multitude of evidence for dietary change following colonisation in the Pacific Islands. Swift et al (2018) reported on changes in diet composition as evidenced by isotope analyses from commensal rats. While Richards et al (2009) found the diet of the Hanamiai population in the Marquesas Islands to be largely terrestrial, Swift et al (2018) identified a decreasingly terrestrial and increasingly marine diet at sites in the Marquesas, with the most significant changes occurring between 1200 and 1400 AD.…”
Section: Diet Subsistence and Adaptationmentioning
confidence: 99%
“…There is a multitude of evidence for dietary change following colonisation in the Pacific Islands. Swift et al (2018) reported on changes in diet composition as evidenced by isotope analyses from commensal rats. While Richards et al (2009) found the diet of the Hanamiai population in the Marquesas Islands to be largely terrestrial, Swift et al (2018) identified a decreasingly terrestrial and increasingly marine diet at sites in the Marquesas, with the most significant changes occurring between 1200 and 1400 AD.…”
Section: Diet Subsistence and Adaptationmentioning
confidence: 99%
“…In particular, as it pertains to Pacific Islands, it may be that the elevation of excavations can undergo a correction model to allow for more precise mixing of broad categories, such as C3 and C4 plant composition. This method could be particularly useful when using localized indicators, such as short-ranged scavengers or local-level sediment collection [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A range of theories have been put forward, including the small size of these bones and potential laboratory contamination at the time of dating [58] [59]. Twenty years later, there have been improvements in our understanding of dietary offsets and application of (dietary and reservoir) corrections to a range of animals that feed in both marine and terrestrial environments, as well as significant improvements in sample pretreatment and the abilities of AMS dating technology to date these tiny samples [60] [9] [61] [62] [63] [64]. The importance of rats as human commensals, as evidenced by their presence in many archaeological deposits including To’aga ([19] pg 200, table 13.3), means there is significant benefit from being able to date these animals directly [65].…”
Section: The To’aga Excavation and Radiocarbon Datesmentioning
confidence: 99%